2015
DOI: 10.1542/peds.2014-3750
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary Time in Late Childhood and Cardiometabolic Risk in Adolescence

Abstract: BACKGROUND AND OBJECTIVE: There is a paucity of prospective evidence examining the links between sedentary time (ST) and cardiometabolic outcomes in youth. We examined the associations between objectively assessed ST and moderate to vigorous physical activity (MVPA) in childhood with cardiometabolic risk in adolescence. METHODS:The study included 4639 children (47% male) aged 11 to 12 years at baseline whose mothers were enrolled in ALSPAC (Avon Longitudinal Study of Parents and Children) during their pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 39 publications
5
71
0
Order By: Relevance
“…Stamatakis et al . observed an inverse association between MVPA and SBP but that association was attenuated by adjustment of important covariates and baseline value of SBP, which corresponded with the four other studies reporting no prospective associations . However, some studies observed inverse associations in boys; Carson et al .…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Stamatakis et al . observed an inverse association between MVPA and SBP but that association was attenuated by adjustment of important covariates and baseline value of SBP, which corresponded with the four other studies reporting no prospective associations . However, some studies observed inverse associations in boys; Carson et al .…”
Section: Resultssupporting
confidence: 79%
“…Similar but weaker findings were observed at the 75th and 50th BMI percentiles . Two studies found that sedentary time predicted lower BMI and WC , even after adjustment of MVPA. In general, studies examining the prospective associations between sedentary time and adiposity reported no evidence for any association .…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…After adjustment for MVPA, a significant negative association was evident between change in sedentary behaviour and change in HDL cholesterol; however, change in total sedentary time was not associated with change in clustered metabolic syndrome score or other individual components. Another longitudinal study found that total sedentary time was not associated with individual or clustered cardio‐metabolic risk in 11‐ to 12‐year‐old children .…”
Section: Resultsmentioning
confidence: 97%
“…Various studies have suggested a number of shortcomings in terms of physical activity in young people that can lead to many health problems, and the universality of their occurrence requires work in the field of public health (Hills et al, 2011;Jodkowska et al, 2015;Stamatakis et al, 2015). Problems associated with lifestyle-related diseases are crucial for most developed countries.…”
Section: Introductionmentioning
confidence: 99%